2018
DOI: 10.1016/j.seizure.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of cEEG as a predictor of patient outcome and survival in patients with intraparenchymal hemorrhages

Abstract: cEEG measures were significantly associated with functional and mortality outcome measures in patients with IPH even after accounting for known clinical and radiological covariates. Further research is needed to determine whether prediction models are improved by inclusion of cEEG features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
8
0
3
Order By: Relevance
“…The obtained data are consistent with the results of other studies. Thus, in the study of M. Purandare et al (2018) it was determined that RSRP levels of δ-, α-ranges, DTABR, DAR in patients with SSICH were associated with Glasgow coma scale score and ICHV [12]. In the study by P. Xu et al (2008) it was revealed that intracranial hypertension and the development of dislocation syndrome in patients with intracerebral hemorrhage are accompanied by the elevation of the absolute spectral power of slow-wave activity with an accented range within 0.5-3.0 Hz [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data are consistent with the results of other studies. Thus, in the study of M. Purandare et al (2018) it was determined that RSRP levels of δ-, α-ranges, DTABR, DAR in patients with SSICH were associated with Glasgow coma scale score and ICHV [12]. In the study by P. Xu et al (2008) it was revealed that intracranial hypertension and the development of dislocation syndrome in patients with intracerebral hemorrhage are accompanied by the elevation of the absolute spectral power of slow-wave activity with an accented range within 0.5-3.0 Hz [18].…”
Section: Discussionmentioning
confidence: 99%
“…The expediency of the detection of these indicators in clinical practice as neurophysiological criteria for the assessment of patients' state severity and markers of the effectiveness of the therapy was justified [1,5,13,14,20]. At the same time, very few papers were devoted to the study of these aspects in patients with SSICH [6,12].…”
Section: а а кузнецовmentioning
confidence: 99%
“…Все викладене обгрунтовує доцільність об'єктивізації функціонального стану церебральних структур у пацієнтів в гострому періоді спонтанного супратенторіального внутрішньомозкового крововиливу (ССВМК) з використанням електроенцефалографічного обстеження [5]. У дослідженнях попередніх років доведена висока діагностична інформативність електроенцефа-лографії у пацієнтів з гострими ушкодженнями головного мозку переважно ішемічного та травматичного генезів [6,7], при цьому вивченню особливостей змін біоелектричної активності головного мозку у пацієнтів з півкульовим геморагічним інсультом присвячені окремі роботи [8,9]. Виявлені взаємозв'язки показників відносної спектральної потужності ритмів електроенцефалографічного патерну з тяжкістю ураження церебральних структур [10].…”
Section: вступunclassified
“…Отримані дані узгоджуються з результатами дослідження Y. Chen [et al] (2018), в якому було виявлено більш високий рівень інтегрального коефіцієнту DAR у пацієнтів з несприятливим вітальним прогнозом виходу гострого періоду геморагічного інсульту внаслідок більш тяжкого ураження церебральних структур [10]. У дослідженні М. Purandare [et al] (2018) було продемонстровано взаємозв'язок між відсутністю передньо-задного градієнту ритмів електроенцефалографічного патерну та гіршим виходом гострого періоду внутіршньомозкового крововиливу [9]. Більш високий рівень абсолютної спектральної потужності ритмів тета1-піддіпазону в інтактній гемісфері порівняно з ураженою, зафіксований у пацієнтів з ЛД>5 мм, на нашу думку відображає явища міжпівкульового діашизу у вказаного контингенту хворих і узгоджується з результатами дослідження G. Assenza [et al] (2013) [11].…”
Section: таблиця 1 аналіз відносної спектральної потужності ритмів (%unclassified
“…Мілісекундна роздільна здатність, яка не доступна таким методам дослідження як позитронна емісійна томографія та функціональна магнітно-резонансна томографія, зробила можливим застосування ЕЕГ для здійснення моніторингу біоелектричної активності головного мозку підчас каротидної ендартеректомії з метою своєчасної верифікації ятрогенної церебральної ішемії [10]. Разом із тим, вивченню ЕЕГ-патерну у пацієнтів зі спонтанним внутрішньомозковим крововиливом присвячені поодинокі роботи, які торкаються переважно аспектів верифікації вітального прогнозу [11][12][13], тоді як розробці ЕЕГ-критеріїв прогнозу функціонального виходу гострого періоду ССВМК на підставі оцінки динамки біоелектричної активності головного мозку приділяється недостатня увага.…”
unclassified